PENGARUH INOVASI PRODUK, SOCIAL MEDIA MARKETING DAN CITRA MEREK TERHADAP MINAT BERKUNJUNG WISATAWAN DAN DAMPAKNYA TERHADAP IMPULSIVE BUYING PADA SEKTOR UMKM KERAJINAN TANAH LIAT DI DESA WISATA GERABAH KASONGAN YOGYAKARTA - Mariah Mariah; Siti Ruhana Dara (JURNAL LENTERA BISNIS, 2020)
This study aims to analyze the effect of product innovation, social media marketing and brand image on the interest of tourist visits and its impact on impulsive buying in the clay craft UMKM sector in the village of Kerabah Kasongan, Yogyakarta. This research has a type of quantitative research with 100 respondents who are consumers. clay crafts. The sampling method was purposive sampling. This study uses quantitative research methods by conducting surveys, the results of validity and reliability tests using SPSS v 20.0, and hypothesis testing is carried out using multiple linear regression methods. The results showed that product innovation had no effect on visiting interest, social media marketing had an effect on visiting interest, brand image had an effect on visiting interest and visiting interest had an effect on impulsive buying.Keywords:  product innovation, social media marketing, brand image, impulsive buying, interest in visiting.